Students' academic language-related challenges in English Medium Instruction: The role of English proficiency and language gain. (December 2021) - Soruç, Adem; Altay, Mehmet; Curle, Samantha; Yuksel, Dogan
Abstract: This article reports a quantitative empirical study that explored the relationship between English language proficiency and academic language-related challenges experienced by students when studying through English Medium Instruction (EMI). Questionnaire data using the EMI Challenges Scale and student English language test score data were collected at a public university in Turkey. Two academic subjects were compared: International Relations (a Social Science subject, n = 99) and Electronic Engineering (a Mathematics, Physical and Life Sciences subject, n = 99). Results revealed that in both subjects, English language proficiency statistically significantly predicted academic language-related challenges. Furthermore, a gain in English proficiency significantly predicted the challenges in International Relations but not in Electronic Engineering. Finally, Electronic Engineering students experienced significantly different levels of linguistic-related challenges in each language skill when at a lower proficiency (A2) compared to a higher proficiency (B2). In International Relations, a proficiency threshold was more evident; students experienced significantly higher levels of linguistic-related challenges as proficiency decreased. Important pedagogical implications of this established relationship between language proficiency, language gain, and language-related challenges in two academic divisions are discussed. Highlights: English language proficiency predicts EMI students' academic language related challenges. The higher English language proficiency, the lower academic language-related challenges regardless of academic subject. Language proficiency threshold varies according to the academic division. There is an apparent proficiency threshold for International Relations students – B2 level of English proficiency.